2015
DOI: 10.13080/z-a.2015.102.005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of potato tubers chemical composition with selected physiological indicators

Abstract: The paper deals with the analysis of a ten-year study on the chemical composition of tubers of forty potato cultivars and their physiological indicators. The research was carried out at the experimental station in Parczew, Poland on a podzolic soil with typical granulometric composition of sandy silty clay, using a randomized block design in four replicates. Forty potato cultivars were the subject of this study, including eight very early, seven early, nine medium early, nine medium late and seven late cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
2
20
1
Order By: Relevance
“…Thus, analysis of chlorophyll fluorescence parameters may serve as a very accurate tool to study photosynthetic reactions under stress conditions and evaluate the effects of adverse environmental factors on plants, which is confirmed by the research results of Sawicka and Michałek (2005), Kuckenberg et al (2009), Kalaji et al (2014;2016 b) and Sawicka et al (2015). At the same time, this technique allows early diagnosis of the impact of a stress factor, before visible stress symptoms occur.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Thus, analysis of chlorophyll fluorescence parameters may serve as a very accurate tool to study photosynthetic reactions under stress conditions and evaluate the effects of adverse environmental factors on plants, which is confirmed by the research results of Sawicka and Michałek (2005), Kuckenberg et al (2009), Kalaji et al (2014;2016 b) and Sawicka et al (2015). At the same time, this technique allows early diagnosis of the impact of a stress factor, before visible stress symptoms occur.…”
Section: Discussionmentioning
confidence: 66%
“…Živčák et al (2014 b; c) also drew similar conclusions on the basis of a study on the effect of nitrogen deficiency on chlorophyll fluorescence in wheat. Sawicka and Michałek (2005) as well as Sawicka et al (2015) have found that differences in photosynthesis efficiency may depend on both leaf inclination and leaf chlorophyll content. A low extinction coefficient allows more effective control of the transfer of solar energy through the leaf canopy.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Plant growth and development and consequently yields are influenced by many stress factors, such as low or high temperatures, water deficit, excessive radiation within the photosynthetically active range, mechanical injuries, gaseous contamination, phytotoxins, herbicides applied, or intensive fertilization (Sawicka et al, 2015). Although potato is the most widely distributed crop in tropical and subtropical zones of the world (Burhan et al, 2007), its productivity and quality are inadequate due to disjointed investigation of the many factors that hinder them.…”
Section: Introductionmentioning
confidence: 99%